Student Housing and Homelessness: A Paradox of Urban Gentrification in Pretoria's Old East, South Africa. Issue 3 (1st October 2020) - Mashayamombe, John; Vally, Rehana
ABSTRACT: The urgency of providing affordable student housing influenced government and higher education institutions to consider urban renewal as a possible avenue to alleviate this demand, with the result that private–public partnerships were promoted to address this. Issues discussed in this article are drawn from qualitative interviews with University of Pretoria's Student Representative Council (2018–2019), a university official and a Pastor as well as an administrator from churches based in Hatfield and Arcadia, Pretoria. This article looks at urban renewal processes in Hatfield (Old East of Pretoria), which is home to the University of Pretoria and argues that the unintended consequences of revanchist gentrification has not sufficiently addressed issues of affordable student housing. Rather, there is evidence of student homelessness.